Study of cold joint concrete by infrared thermography and ultrasonic pulse velocity - Mohamed Luqman, Mohamed Roslan (2017)
Infrared thermography (IRT) has been used in civil engineering field such as highway, bridge and concrete structure. IRT provides non-destructive method to analyse defects on structure including crack. Cold joints are formed primarily between two batches of concrete where the delivery and placement of the second batch has been delayed and the initial placed and compacted concrete has started to set. The full knitting together of the two batches of concrete under vibration to form a homogeneous mass is therefore not possible, unlike the compaction of two fresh workable batches of concrete. This could be a potential plane of weakness. The objective of this research are to analyse the cold joint of concrete when loading applied and to determine uniformity of cold joint concrete using Ultra Pulse Velocity (UPV). Thermography is specialized in subsurface damage identification due to anomalies that inhomogeneity impose on the temperature field. Additionally, ultrasonic waves are constrained near the surface and therefore, are ideal for characterization of near-surface damage. In this study, an infrared camera scans cold joint beam structure and analyse crack happen at cold joint during loading. Colour summarization software will analyse the colour at cold joint and the entire beam. Through software, the difference of colour could be seen between the crack section and non-crack section. Based on the research, infrared images produced does not differentiate between cold joints section and other part of beam. Through flexural test it is found that crack formed through the cold joint as there is no other part of beam produced crack when loading applied. Unfortunately the infrared camera cannot capture the image which have brighter colour such as red, orange or yellow. The colour of the beam become blue because the machine of flexural test more dominant in temperature so the colour of one part of the machine brighter than the beam. Behind the machine itself, sunlight penetrate through the windows. Based on Ultra Pulse Velocity result, pulse velocity concrete casting day 1, day 2 and at the cold joint are higher than 4 km/s which means concrete quality is good and the speed is uniform. The UPV reading at cold joint have a decreasing trend compared to reading at same day casting section. In conclusion, the colour summarization of beam using IRT image cannot be achieved as the colour have little variation. As for UPV result, at cold joint section the reading is smaller compared to section casting on the same day and it is still under good category for time lag 24 hours.